A PALAVRA DE JAVÉ EM JEREMIAS 7,1 8,3: UMA ANÁLISE DA PROFECIA COMO PORTADORA DE UM CONFLITO SOCIAL ORIUNDO DA COBRANÇA EXCESSIVA DE TRIBUTO - Salgado, Samuel de Freitas (2014)
This research focuses on the historical approach to analyze the biblical text as a historical-social product, from the sociological method. The material arranged along this research is intended to be an aid to understanding some texts from the prophet Jeremiah. Assuming that the text has a link with the society in which it was created and making use of exegetical methodology, carried out a historical-sociological analysis of the word of Yahweh in Jeremiah from 7,1 8,3 as carrier of a social conflict arising from excessive tribute collection on a Judahite society markedly tributary. It seeks, through this, the meaning of the text within the historical setting likely that permeated the social writing. For this, it is necessary to research the primary aspects involving both the book of Jeremiah, especially the controversial caps. 7,1 8,3, as well as the question of modern research study about this magnificent work. It is also worth highlighting the semiotic concept of sociological poetics that seeks to study the causal interaction between literature and the social environment. Moreover, it evaluates the social historical context of the literary unit target of our research, situating it in its likely social and historical context, determining the date, the political scene and the production mode current at this time. Not forgetting, however, the triggering factor of social conflict and the role of religion in this scenario. Furthermore, it examines the meaning of specific texts or completed literary units (pericopes) present in caps. 7,1 8,3, with the assumption the theoretical model of the tributary production mode and the steps of the social-historical exegesis. The social analytical mechanism of the tributary production mode will serve as a tool for analysis of socioeconomic status, such analysis is focused on the external components incorporated in the collection, not in its editorial history, but in its social formation.